Economic issues and policy - Brux, Jacqueline Murray (South-Western Cengage Learning, 2011)
This book provides students with a grasp of basic economic tools through the analysis of important economic issues and their related policy perspectives. Economic theory is presented in a simple, market-oriented framework at a level of technicality that is deliberately appropriate for a basic first course in economics directed at non-majors. Complex topics more appropriate for a Principles of Economics course are left out or contained in appendices. In analyzing economic situations and the implications of policies, liberal and conservative viewpoints are effectively balanced -- the careful presentation of conservative and liberal viewpoints is one of the unique characteristics of this book